The Role of Human Resource Management Strategies in Improving Work Productivity Among Employees at PT Koncota Agro Mandiri in Gurusinga Village - Ega Emanda Br Ginting; Menanti Br Sembiring; Ingan Ukur Br Sitepu (Indonesian Journal of Advanced Research, 2026)
This study aims to analyze the role of human resource management (HRM) strategies in improving employee work productivity at PT Koncota Agro Mandiri, Gurusinga Village. As an agribusiness enterprise, managing a diverse workforce is critical to maintaining operational stability. This research employs a descriptive qualitative method. Data were gathered through in-depth interviews with 13 key informants, direct observations, and documentation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. Data trustworthiness was validated using source, technique, and theoretical triangulation. The results indicate that the implemented HRM strategies include workforce planning, technical and non-technical training, compensation schemes, and rigorous supervision. Although training distribution remains sub-optimal due to time and budget constraints, overall HRM strategies play a significant role in enhancing employees' work quality, quantity, and accountability. The company is advised to expand training access for non-permanent workers and address incentive disparities to ensure sustainable productivity.